Economical Measures against Soft Ground at High Embankment on Peaty Ground - Hijiri Hashimoto; Hirochika Hayashi; Atsushi Hirose; Keita Matsuda (Indonesian Geotechnical Journal, 2023)
Peat, which is considered a special soil, is widely distributed over approximately 2,000 km2 in Hokkaido, Japan. In terms of engineering properties, peat is extremely high in water content, ignition loss, and void ratio and extremely in low shear strength. Ground improvement methods using cement are effective for the rapid construction of embankments on peaty ground. However, to avoid differential settlement and lateral flow, most of such construction is carried out with an improvement ratio of ap=50%. In this case, the improvement can certainly be expected to be effective. However, it is less economical than other soft ground improvement methods. The challenge is to reduce the cost of improving the ground. Our institution (the Civil Engineering Research Institute for Cold Region, PWRI) has developed an economical measure against soft ground that uses cement with a reduced improvement ratio in combination with a crushed-stone mat (gravel foundation reinforcement), and we conducted the test construction of a 16-meter-high embankment to verify effectiveness of the method. The crushed-stone mat consists of a 50-cm layer of crushed stone covered with a geo-synthetic material. The test construction achieved the following results. (1) Settlement of the embankment was significantly reduced. (2) Slip failure did not occur. (3) Displacement to the surrounding ground did not occur. (4) The geotextile in the crushed-stone mat exhibited less strain than that which would cause the geo-synthetic to exceed its design strength. These results show that this economical measure against soft ground was effective at stabilizing the high embankment constructed on peaty ground.